Measuring True Sales and Underreporting with Matched Firm-Level Survey and Tax Office Data - Zhou, Fujin; Oostendorp, Remco (The Review of Economics and Statistics, 2014)
This paper uses firm-level survey data matched with official tax records to estimate the unobserved true sales of formal firms in Mongolia. Taking into account firm-level incentives to comply with taxes and a production function technology linking unobserved true sales with observable firm-level production characteristics, we derive a multiple-indicators, multiple-causes model predicting true sales. We find that firms underreport sales to the tax office by 38.6%, but firm-level survey data also suffer from significant underreporting. Finally, we compare our approach with two alternative approaches of measuring underreporting and discuss the practical implications of the findings for firm-level analyses of underreporting.